POLA JUMLAH TROMBOSIT PENDERITA DEWASA TERINFEKSI VIRUS DENGUE DI RSUD DR.SOETOMO SURABAYA - Afgriyuspita, Lelyana Sih; Kahar, Hartono; Sudiana, I Ketut (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
ABSTRACT The trend of dengue viral infection in Indonesia and several countries has changed from children to older age groups. Thrombocytopenia is a common laboratory parameter used to diagnose dengue virus infection that has the possibility to change day by day. This research was expected to improve understanding thrombocyte pattern in adult patients. This was a descriptive study with a retrospective design using medical records of Dr. Soetomo general hospital Surabaya during 2017-2018. The sample used was adult patients in the age range of 18-55 years old with Dengue Fever (DF) or Dengue Haemorrhagic Fever (DHF). The sampling technique was total sampling and obtained 62 samples. Data was analyzed using an independent t-test and Mann-Whitney. The pattern of average thrombocyte count decreased on the 3rd day till the 6th day. Entering the 7th day, it increased but did not reach the normal value. There were significant differences in the average of thrombocyte count between DF and DHF patients during the 4th day (p=0.003), 5th day (p = 0.006) and the 6th day (p= 0.014). Decreased thrombocyte count < 100,000/µL in DHF patients should be intensively observed starting from the 3rd day of illness. Keywords : DF,DHF, thrombocyte,adult